Effect of intravitreal VEGF inhibitors on renal-related adverse events in patients with diabetes mellitus: systematic review and meta-analysis - Zheng, Yu; Zhang, Fan; Li, Xueling; Zhang, Xianwen; Zhong, Yifei (Frontiers in Pharmacology, 2025)
BackgroundIntravitreal vascular endothelial growth factor inhibitors (VEGFis) are a standard treatment for diabetic eye complications. However, concerns persist regarding their potential nephrotoxic effects in patients with diabetes mellitus (DM), who are inherently at increased risk of renal disease due to diabetes-related microvascular damage.MethodsWe systematically searched PubMed, Embase, and Cochrane Library for randomized controlled trials (RCTs) evaluating renal-related adverse events in DM adults receiving intravitreal VEGFis versus controls. The primary outcome was occurrence of acute kidney injury (AKI), and the secondary outcome was the risk of chronic kidney disease (CKD). Fixed-effects models pooled odds ratios (ORs) with 95% confidence intervals (CIs).ResultsFrom 16 RCTs (n = 5,930 patients), pooled analyses showed no significant increase in renal risk with VEGFis. The incidence of AKI (10 trials) showed no significant difference between the VEGFis groups (2.0%) and controls (1.5%; OR = 1.07, 95% CI: 0.65–1.75; GRADE very low quality). Similarly, the incidence of CKD (15 trials) was comparable in VEGFis groups (2.4%) versus controls (2.1%; OR = 1.11, 95% CI: 0.75–1.64; GRADE very low quality). Subgroup analyses of AKI incidence stratified by VEGFis types, injection numbers, and treatment duration showed similar event rates across all subgroups, with no statistically significant differences observed.ConclusionCurrent evidence does not indicate a clear increase in the risk of AKI or CKD with intravitreal VEGFis in adults with DM, but the certainty is very low, and high-risk subgroups remain insufficiently studied.